2019
DOI: 10.1111/jpn.13097
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus faecium NCIMB 10415 supplementation improves the meat quality and antioxidant capacity of muscle of broilers

Abstract: The present study was conducted to investigate the effects of Enterococcus faecium (E. faecium) on the meat quality and antioxidant capacity of muscle in broilers. A total of 600 Arbor Acre broiler chickens (1‐day‐old, male) were randomly divided into five treatments with six replicates (20 chickens per replicate) for each treatment. The five treatments were the control treatment (CON, basal diet), antibiotic treatment (ANT, basal diet supplemented with 0.1% chlortetracycline) and E. faecium‐supplemented treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
3
12
0
1
Order By: Relevance
“…Probiotics and active substances may play an important role in the effect of dietary FMLP on meat color of broilers. This conjecture is consistent with the findings of Yu et al [ 35 ], who reported that dietary supplementation of high concentrations had the most significant effect on meat color [ 35 , 36 , 37 ], and the findings of Shen et al [ 38 ], who revealed that the effect of adding bamboo leaf extract in the diets with different concentrations on meat color was linearly increased [ 38 ]. Tenderness (shear force) may be the most important edible quality parameter that determines consumer acceptance [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Probiotics and active substances may play an important role in the effect of dietary FMLP on meat color of broilers. This conjecture is consistent with the findings of Yu et al [ 35 ], who reported that dietary supplementation of high concentrations had the most significant effect on meat color [ 35 , 36 , 37 ], and the findings of Shen et al [ 38 ], who revealed that the effect of adding bamboo leaf extract in the diets with different concentrations on meat color was linearly increased [ 38 ]. Tenderness (shear force) may be the most important edible quality parameter that determines consumer acceptance [ 39 ].…”
Section: Discussionsupporting
confidence: 91%
“…Probiotics in fermented mulberry leaf powder may play an important role in it. Previous studies similarly have found that dietary supplementation probiotic can reduce muscle shear force [ 35 , 41 ]. Relative to the control group, the muscle shear force of MLP group was significantly increased, which may be related to the increase of ADG, resulting in the increase of muscle fiber diameter, which in turn led to the increase of shear force, because the smaller the muscle fiber diameter is, the more tender the muscle is [ 42 ].…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, we found that dietary supplementation with E. scaber increased IMP content in the breast muscle. IMP is one of the major contributors to flavor in meat (24). This result further confirmed that dietary supplementation with E. scaber increased the meat quality of ducks.…”
Section: Discussionsupporting
confidence: 76%
“…Zhou et al (2014) reported that dietary supplementation with 1% the combination of zeolite and attapulgite significantly increased CAT activity and decreased the MDA content of broiler. Yu et al (2019) demonstrated that dietary 100 mg/kg of Enterococcus faecium significantly increased CAT, GSH-Px, and T-AOC activities in the breast meat of 42 day-old broilers. Our previous research on laying hens found that Bacillus subtilis and montmorillonite supplementation on plasma T-AOC and the activity of CAT in the spleen have a significant interaction effect ).…”
Section: Discussionmentioning
confidence: 90%